1989
DOI: 10.1037/0021-843x.98.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Relations of sociotropic and autonomous personality characteristics to specific symptoms in depressed patients.

Abstract: A number of writers have suggested that two sets of personality characteristics are associated both with vulnerabilities to depression in response to different classes of events and with different clinical presentations of depression. The present study examined the relations between levels of sociotropic and autonomous personality characteristics and specific, theoretically derived clusters of symptoms in 80 unipolar depressed patients. As was predicted, sociotropy was related to the cluster of symptoms associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
5
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 7 publications
8
68
5
1
Order By: Relevance
“…The Sociotropy-Autonomy Scale [SAS; Beck et al, 1983] was used to measure the cognitive styles of sociotropy (characterized by a strong need for close relationships, interpersonal dependency, and concern about disapproval) and autonomy (characterized by a heavy emphasis on personal independence and need for control). Excellent internal consistency, as well as test-retest reliability and construct validity, has been reported for this measure [Hammen et al, 1989;Robins et al, 1989]. Based on prior work that showed the superiority of need for control (an autonomy subscale) to the full scale in predicting depression [Mazure et al, 2001], the need for control subscale was used in our analyses.…”
Section: Methodsmentioning
confidence: 93%
“…The Sociotropy-Autonomy Scale [SAS; Beck et al, 1983] was used to measure the cognitive styles of sociotropy (characterized by a strong need for close relationships, interpersonal dependency, and concern about disapproval) and autonomy (characterized by a heavy emphasis on personal independence and need for control). Excellent internal consistency, as well as test-retest reliability and construct validity, has been reported for this measure [Hammen et al, 1989;Robins et al, 1989]. Based on prior work that showed the superiority of need for control (an autonomy subscale) to the full scale in predicting depression [Mazure et al, 2001], the need for control subscale was used in our analyses.…”
Section: Methodsmentioning
confidence: 93%
“…Some studies have failed to find specific associations between either dependency or autonomy and their predicted symptom clusters (Klein, Harding, Taylor, & Dickstein, 1988;Ouimette & Klein, 1993;Persons, Burns, Perloff, & Miranda, 1993). Some studies have found support only for dependency (Allen, Ames, Layton, Bennetts, & Kingston, 1997;Clark, Steer, Haslam, Beck, & Brown, 1997;Haslam & Beck, 1994;Robins, Block, & Peselow, 1989;Zuroff & Mongrain, 1987), one has found support only for autonomy (Persons, Miranda, & Perloff, 1991), and several have found support for both (Peselow, Robins, Sanfilipo, Block, & Fieve, 1992;Robins & Luten, 1991;Robins, Bagby, Rector, Lynch, & Kennedy, 1997). Moreover, in some studies, the specific associations obtained between the personality dispositions and symptoms did not correspond directly to those initially hypothesized.…”
mentioning
confidence: 91%
“…One such measure, the Personal Style Inventory (PSI; Robins et al, 1994), has two subscales called sociotropy and autonomy, which have been shown to represent a vulnerability to different types of depression (i.e., exogenous and endogenous; Peselow, Robins, Sanfilipo, Block, & Fievre, 1992) or, at least in unipolar depression, a vulnerability to depression in response to different types of life event (i.e., interpersonal or achievement; Hammen, Ellicott, Gitlin, & Jamison, 1989). The PSI has been found to be related to measures of depression and depressive symptoms (Robins, Block, & Peselow, 1989;Robins & Luten, 1991) as well as to other measures of depressive vulnerability, such as the Depressive Experiences Questionnaire's dependency and self-criticism subscales (Robins et al, 1994). However, despite criticism that too little attention has been paid to the question of whether measures such as sociotropy and autonomy are specifically related to depression or are markers of more general vulnerability (Watson, Clark, & Harkness, 1994), the PSI has not been widely examined in conjunction with anxiety diagnoses, especially in conjunction with measures of vulnerability to anxiety disorders.…”
Section: Introductionmentioning
confidence: 98%